2019
DOI: 10.1038/s41438-019-0138-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and molecular analysis of nonuniform anthocyanin pigmentation in tomato fruit under high light

Abstract: Pigment intensity and patterns are important factors that determine the nutritional and market values of tomato fruits. The acropetal manner of light-dependent anthocyanin accumulation with the highest levels at the stem end of the fruit makes Pro35S:BrTT8 tomato plants an ideal system for investigating the effects of light intensity on anthocyanin biosynthesis. Extensive transcript analyses indicate that anthocyanin pigmentation in Pro35S:BrTT8 plants under high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 61 publications
(81 reference statements)
4
34
0
Order By: Relevance
“…Unexpectedly, the expression level of CaMYB101 in purple areas of pTRV2::CaMYB101 ovaries was also significantly higher compared to green parts of pTRV2::CaMYB101 ovaries, as well as in green pTRV2::GUS ovaries (Figure 7B). The high expression level of CaMYB101 in the purple area of pTRV2::CaMYB101 ovaries is in line with a study that also reported a high expression level of its tomato orthologous gene SlMYBL2 in purple fruits of transgenic tomato lines overexpressing BrTT8 (Zhang et al, 2019), suggesting that SlMYBL2 was transcriptionally activated to counterbalance the active transcription of the MBW complex to prevent excessive anthocyanin synthesis. Zhang et al (2019) proposed that an excess of anthocyanin synthesis could act as a signal to activate the expression of SlMYBL2 .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Unexpectedly, the expression level of CaMYB101 in purple areas of pTRV2::CaMYB101 ovaries was also significantly higher compared to green parts of pTRV2::CaMYB101 ovaries, as well as in green pTRV2::GUS ovaries (Figure 7B). The high expression level of CaMYB101 in the purple area of pTRV2::CaMYB101 ovaries is in line with a study that also reported a high expression level of its tomato orthologous gene SlMYBL2 in purple fruits of transgenic tomato lines overexpressing BrTT8 (Zhang et al, 2019), suggesting that SlMYBL2 was transcriptionally activated to counterbalance the active transcription of the MBW complex to prevent excessive anthocyanin synthesis. Zhang et al (2019) proposed that an excess of anthocyanin synthesis could act as a signal to activate the expression of SlMYBL2 .…”
Section: Discussionsupporting
confidence: 86%
“…To identify anthocyanin-related R2R3-MYB repressors in pepper, a phylogenetic analysis was performed using candidate pepper MYB repressors together with 36 published anthocyanin MYB regulators from other plant species (Table 3, Figure 4). Meanwhile, CaMYB101, CbMYB89 and CcMYB92 were characterized within one cluster (red curve in Figure 4), together with two identified R2R3-MYB repressors from the Solanaceae family (petunia PhMYB27 and tomato SlMYBL2) (Albert et al, 2011; Zhang et al, 2019). In addition, two strawberry R2R3-MYB repressors (FaMYB1 and FcMYB1) and one Medicago truncatula R2R3-MYB repressor (MtMYB2) were the closest orthologs to the cluster of CcMYB87, CcMYB108, CbMYB67 and CaMYB70 and the cluster of CaMYB101, CbMYB89 and CcMYB92.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MBW transcriptional regulators are generally conserved in regulating the expression of anthocyanin biosynthetic genes in eudicots [ 37 , 38 ]. We found that the mRNA levels of BrLETM2 and BrPAP1.3 genes can be induced after UV-A irradiation ( Figure 6 F, Figure S4 ), but the mRNA level of BrPAP1.3 dramatically decreased in the g120w mutant ( Figure 1 F).…”
Section: Discussionmentioning
confidence: 99%
“…The anthocyanin biosynthetic pathway is a branch of the flavonoid pathway in plants (Huang et al, 2016). Following phenylpropane synthesis, anthocyanins are synthesized in the cytoplasm by 4-coumarate-CoA and malonyl-CoA, which is catalyzed by enzymes encoded by a series of structural genes, including CHS, CHI,F3H,F3'H,F3'5'H,DFR,ANS,and 3GT, followed by modifications of glycosylation, methylation, and acylation to form stable anthocyanins and allow entry into the vacuole, in a process mediated by glutathione S-transferase (GST) and MATE-type transporters (Vogt, 2010;Zhang et al, 2019;Luo et al, 2018). Anthocyanin synthesis is mainly regulated by MBW complexes including MYB, basic helix-loop-helix (bHLH), and WD40-repeat proteins, as well as other transcription factors such as bZIP and WRKY (Xu et al, 2014;Gelderen et al, 2018;Gonzalez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%